2014
DOI: 10.1016/j.otsr.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Bone scan as a screening test for missed fractures in severely injured patients

Abstract: Level IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…From previous researches, rib fractures were identified in 7∼ 40% of multiple trauma cases [8][9][10][11] In conclusion, WBBS was useful for detecting missed bone injuries in patients with multiple traumas.…”
Section: Discussionmentioning
confidence: 77%
“…From previous researches, rib fractures were identified in 7∼ 40% of multiple trauma cases [8][9][10][11] In conclusion, WBBS was useful for detecting missed bone injuries in patients with multiple traumas.…”
Section: Discussionmentioning
confidence: 77%
“…This report represents one of the first cases of “ de novo ” atraumatic pedicle insufficiency bilateral fractures without any pre-existing biomechanical risk factors. We believe this type of fracture is easily overlooked on plain radiographs if undisplaced, 21 thus justifying advanced modalities if suspected. It may be associated with subsequent development of lytic spondylolisthesis, though the strength of such an association is not clear.…”
mentioning
confidence: 93%
“…Hence, there is a limitation of concomitantly evaluating the co-existing musculoskeletal injuries during the initial resuscitation and assessment. Previously, many studies have reported the missed bone fractures in polytrauma patients with high incidences [ 2 , 4 , 13 , 15 , 20 , 21 ]. However, there is a few studies specifically addressing the combined skeletal trauma in patients with traumatic brain injury (TBI) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A whole body bone scan (WBBS) is one of the useful diagnostic techniques to assess the multiple number of traumatic lesions in the whole skeletal system without invasive technique [ 5 , 13 ]. As mentioned earlier, the combined skeletal trauma in patients with TBI can be overlooked due to their altered neurologic states.…”
Section: Introductionmentioning
confidence: 99%